Problematizações sobre o movimento da criança na Educação Infantil - Pereira, Bruna Fernanda (Universidade Federal de São Carlos, 2025)
The present study aimed to problematize which institutional and pedagogical factors may contribute to the restriction of children's movement in Early Childhood Education, which may have consequences for their overall development, and understand the importance of playful movements and corporeality for children. To this end, a qualitative, bibliographical and exploratory research was carried out, reflecting on the experiences lived by the author during her supervised internship in Early Childhood Education. The study explores, based on Bourdieu's theoretical contributions, especially the concept of habitus, how the school, as a social institution, acts to regulate children's movements, shaping them socially. It also discusses how school culture restricts play and movement in its practices and experiences, contradicting the principles of Brazilian educational legislation, which recognizes playful movement as the main activity of children in Early Childhood Education for their development and learning in early childhood. The work seeks to emphasize the importance of movement in pedagogical practices, valuing children's bodily manifestations as language, learning and development throughout Early Childhood Education.
Problematizations about children's movement in Early Childhood Education
Keywords: Movimento; Brincar; Educação infantil; Corporeidade; Movement; Play; Early childhood education; Corporeality; CIENCIAS HUMANAS::EDUCACAO